2015
DOI: 10.2147/gictt.s51386
|View full text |Cite
|
Sign up to set email alerts
|

New insights from animal models of colon cancer: inflammation control as a new facet on the tumor suppressor APC gem

Abstract: Colorectal cancer (CRC) is one of the most common causes of cancer-related deaths worldwide. As with other cancers, CRC is a genetic disease, however, several risk factors including diet and chronic colitis predispose to the disease. Mutations in the tumor suppressor adenomatous polyposis coli (APC) initiate most cases of CRC. Recent data from mouse models suggest that APC mutations and colitis are not completely independent factors in colorectal carcinogenesis. Here, we review the evidence supporting an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 189 publications
0
4
0
Order By: Relevance
“…The precise function of APC in these APC high goblet cells has yet to be determined. We and others have reported that APC promotes goblet cell differentiation and mucosal barrier integrity (van de Wetering et al, 2002;Zeineldin & Neufeld et al, 2015). In terms of goblet cell differentiation, APC has been shown to target CtBP1 for degradation (Nadauld et al, 2006) and CtBP1 is a transcriptional co-repressor of a goblet cell-specific differentiation factor, KLF4 (Katz et al, 2008;Liu, Zheng, & Ai, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The precise function of APC in these APC high goblet cells has yet to be determined. We and others have reported that APC promotes goblet cell differentiation and mucosal barrier integrity (van de Wetering et al, 2002;Zeineldin & Neufeld et al, 2015). In terms of goblet cell differentiation, APC has been shown to target CtBP1 for degradation (Nadauld et al, 2006) and CtBP1 is a transcriptional co-repressor of a goblet cell-specific differentiation factor, KLF4 (Katz et al, 2008;Liu, Zheng, & Ai, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…AvrA also activates STAT3 pathways which are promoting inflammation-associated colonic tumorigenesis [25]. Inflammation activates many pathways including the NF-kB pathway that synergize with Wnt signal activation which maintains stemness and activates cancer stem cells [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…The protein sequence and domain structure in APC are evolutionary conserved between murine and humans with 89% identity and 91.9% similarity shared at the amino acid level [ 144 ]. This high conservation made murine widely used models investigate the role of Apc in colorectal cancer—at least 43 different mouse models and 3 rat models have been established [ 173 , 174 , 175 , 176 ] ( Figure 3 ). The first genetically engineered mouse model, known as Apc Min (for multiple intestinal neoplasia), contains a nonsense point mutation in the codon 850 that behaves as autosomal dominant loss of Apc function [ 177 , 178 ] and promotes intestinal adenomas (polyps).…”
Section: Apc Functional Domain Analysis and Animal Models For Invementioning
confidence: 99%
“…New animal models to design selective Apc deletions, e.g., use of the LoxP-Cre system or CRISPR genome-editing would help dissect the precise contributions of Wnt and cytoskeletal activities to gut homeostasis. Further, such mutants will shed light into the long-standing question of whether both of these APC activities are mechanistically connected [ 173 , 174 , 175 ].…”
Section: Apc Functional Domain Analysis and Animal Models For Invementioning
confidence: 99%